Efficacy of intramuscular meperidine hydrochloride versus placebo in experimental foot lameness in horses. (December 2013) - Foreman, J. H.; Ruemmler, R.
Summary: Reasons for performing study: There are no peer reviewed, blinded controlled studies regarding the skeletal analgesic efficacy of intramuscularly administered meperidine in horses. Objectives: Using an adjustable heart bar shoe model of equine foot pain, the objective of this study was to test the hypothesis that meperidine (pethidine) administered intramuscularly would prove more efficacious in alleviating lameness than a saline placebo. Study design: Crossover pharmacodynamic experiment. Methods: Eight healthy adult Thoroughbred horses randomly underwent weekly i.m. treatments 1 h after lameness induction: saline placebo (1 ml/45 kg bwt) or meperidine hydrochloride (1 mg/kg bwt i.m.). Heart rate (HR) and lameness score (LS) responses were assessed by a blinded observer every 20 min for 5 h after lameness induction and then hourly through 12 h after treatment. Jugular venous blood samples were obtained at ‐1, 0, 0:05, 1, 2, 4, 6, 8, 10 and 12 h and were subsequently analysed for drug concentrations (lower limit of detection, 1 ng/ml). Repeated measures ANOVA and post hoc  Tukey's test were used to identify analgesic effects at a significance level of P<0.05. Results: Mean (± s.e.) HR were lower in meperidine trials at 2.3, 3.3 and 3.7 h post administration (P<0.05). Mean LS were lower in meperidine trials at 2.0, 2.3 and 3.3 h post administration (P<0.05). Mean plasma (meperidine) peaked at 227 ± 52 ng/ml at 1 h post administration and decreased to 2.7 ± 0.3 ng/ml at 12 h post administration. In 3 of 8 subjects, plasma (meperidine) was below the lower limit of detection at 12 h after administration. Conclusions: Intramuscular meperidine was more effective than the saline placebo but only for 2.0–3.7 h post administration compared with the 8–12 h durations of efficacy reported previously using this same model when horses were treated with nonsteroidal anti‐inflammatory drugs (NSAIDs). Meperidine may be a suitable nonNSAID alternative analgesic for acute foot pain with efficacy lasting from 2–3 h after a single i.m. dose.